Arzobispado de Manila archives a preliminary guide - Libang, Virginia D.; Hidalgo, Namnama P.; Medina, Isagani R. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
Arzobispado de Manila Archives: A Preliminary Guide attempts to record and organize 1,670 ecclesiastical bundles of documents dating between 1581 and 1963 available in the Archdiocese of manila Archives now housed in San Carlos Seminary, Guadalupe, Makati, Rizal. This checklist serves as a finding aid, a guide to, and an inventory of the manuscripts and unpublished documents, while at the same time it unearths the vast mass of historical materials and claims "continuing interest in bibliographic tools for historical source materials."
This preliminary guide lists the documents alphabetically by series titles in Spanish. Under each series, the physical volumes or bundles are identified in chronological order. A total of 319 series titles are listed. About 29 bundles of more current documents now also in the Archives were not listed because these documents had not been sorted and classified when the present guide was being compiled.
An alphabetical index by subject in English and a classified listing of the 319 series according to the categories established by the Los Angeles Chancery Archives (Episcopal Records, Ecclesiastical Records and Miscellaneous Records) have been provided after the main body.
This work hopes to contribute to the continuing bibliographic control of church archives in the Philippines and towards a comprehensive inventory of religious institutional archives and manuscript collections. Such a goal is essential for Philippine historiography. It is also hoped that this preliminary checklist will be useful as the Archdiocese of manila takes significant steps for the technical organization of its archives not only for historical purposes but also for contemporary church government and administration.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Archives, Diocesan; Arzobispado de Manila Archives; Arzobispado de Manila Archives -- Bibliography; Church records and registers -- Philippines